Rancangan Penempatan Modul Surya dan Simulasi PLTS Fotovoltaik Atap Gedung RSPTN Rumah Sakit Universitas Udayana - Merta, Kadek Hari; Kumara, I. N. S.; Ariastina, W. G. (Majalah Ilmiah Teknologi Elektro; Vol 18 No 3 (2019): (September - Desember) Majalah Ilmiah Teknologi Elektro, 2019)
Indonesia consumed large amount of electrical energy which mostly generated using conventional resources which was dimisihing. Therefore, government released national energy policy aimed at reducing the use of fossil-based energy and increasing the role of renewable energy. One of the renewable energy source was solar photovoltaic. Udayana University had the potential to develop photovoltaic system on all of its premises and one of them was Udayana Hospital. In this research, a study on the potential of rooftop PV at Udayana University Hospital was presented. It was found that the hospital had the potential to generate total electrical power of 835,560 Wp. Our study showed that Building #1 can potentialy generate 142,560 Wp on its rooftop which capable to supply 31.32% of energy consumption in the building. It was found Building #1 could produce energy of arround 166,407 kWh annualy that was equal to 22.6% of the electrical energy consumption of the building. By incorporating the roof of ground car parking canopy, the PV system could generate total power of 226,710 Wp which was equal to 46.98% of Building #1 total power when it was fully operational. It was estimated that this the combination of rooftop and parking PV could generate energy of 249,610 kWh annualy which was equal to 32.8% of the electric energy consumption of Building.